Peran Kepemimpinan Transformasional Kepala Sekolah Era Society 5.0 di SMK Negeri 1 Surabaya - Rozi, Moch. Mu’thi Fathur; Badriyah, Laila (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The role of leadership is needed to encourage the progress and transformation of the educational environment, The principal's transformational leadership is an aspect of innovation, and the creativity of the principal to carry out a leadership role, coupled with the start of the Society 5.0 era, where technological advances cannot be separated from everyday life. Transformational leadership style is the spirit of a leader in transforming to make changes that are different from before, from potential energy to real energy in the form of motivation. In accordance with the research focus raised, the authors in this study used field research with a descriptive research type and a qualitative approach. This type of research uses field research that is qualitative-descriptive in nature, namely research procedures that produce descriptive data in the form of written words or utterances from people and observable behavior. There are three aspects in the form of transformational leadership. important principles are attitude, self-concept, goals. There are three aspects in the process of forming school principals' transformational leadership, namely creativity, collaboration, and discussion. Important forms of transformational leadership of school principals are attitudes, self-concept, goals. This is a form of transformational leadership that must be owned by the principal of SMK Negeri 1 Surabaya. The process of forming the principal's transformational leadership is applied by the principal at SMK Negeri 1 Surabaya in order to create transformational leadership through creativity, collaboration, and discussion.